Chủ tịch Hồ Chí Minh và Cách mạng Pháp 1789 - Đỗ, Quang Hưng (Hà Nội, 2013)
The words "freedom, equality, fraternity" had a strong impact on President Ho Chi Minh even when he still 13. He came to France to study the abundant experience of the French Revolution of 1789 which he believed would be a great help In the liberation of the Vietnamese people from the yoke of slavery by the Frech themselves. The article present In detail and publicires some new documents about the period of President Ho Chi Minh's activities during the time he was abroad and his translation of the advanced ideas and experience of the French Revolution of 1789 into an acute ideological weapon for the hard long struggle of the Vietnamese people.